What does it feel like to be post-secular? Ritual expressions of religious affects in contemporary renewal movements - Richman, NI (Taylor and Francis, 2018)
This paper seeks to problematise and complexify scholarly accounts of contemporary emotional repression in Western contexts by presenting counterevidence in the form of two examples of post-secular collective affectivity and their ritual expressions. It argues that both narratives of emotional repression and expression fail to capture the non-linear complexity of processes of cultural transformation, which have resulted in the simultaneous expression and repression of ritualistic affects that are products of our evolutionary embodied history. Drawing on insights from affect theory, this paper seeks to illustrate how contingent yet nonetheless residual ritualistic affects have become repressed in the nominally secular public sphere in modernity. This has presented certain obstacles to the open communal display of religious ritual, and, as a corollary, the expression of certain religious affects, which have subsequently re-emerged in post-secular ritual spaces that are both publically private and privately public, carved by contemporary renewal movements. Two of these ‘formations of the post-secular’ are explored here: the Sunday Assembly, a secular church, and Mountain of Fire and Miracles Ministries, an international Pentecostal Deliverance church.